2013
DOI: 10.1155/2013/486593
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Diastolic Evaluation in Pregnant Women with Abnormal Glucose Tolerance: An Opportunity to Detect the Early and Subclinical Alterations and Prevent Cardiovascular Diseases

Abstract: Objectives of this study were to assess diastolic function in pregnant women with abnormal glucose tolerance (AGT), compared with normal glucose tolerance (NGT) women, and to evaluate the insulin resistance status and its association with Doppler-echocardiographic indexes. Echocardiograms of 108 consecutive Caucasian women with singleton pregnancies were performed. Insulin resistance status was estimated by the homeostasis model assessment of insulin resistance (HOMA-IR) and the quantitative insulin sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Our findings are corroborated by the results of two other studies. 17,30 The tissue parameters of diastolic function (E′ and A′) have a higher accuracy for this analysis because they are relatively load-independent and thus suitable for evaluation of ventricular overload states, such as pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are corroborated by the results of two other studies. 17,30 The tissue parameters of diastolic function (E′ and A′) have a higher accuracy for this analysis because they are relatively load-independent and thus suitable for evaluation of ventricular overload states, such as pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference of rate of gestational diabetes between Impaired cardiac diastolic function group and normal cardiac diastolic function group (9.1% vs. 8.4%, p = 0.833). Previous study 27 showed that abnormal glucose tolerance was associated with higher A wave but had no influence on E/A ratio or Em, indicating Glucose metabolic disorders might influence cardiac diastolic function. Further study is worth to explore the relation between Glucose metabolism, hypertensive disorder and cardiac function.…”
Section: Discussionmentioning
confidence: 91%
“…Pintaudi et al reported lateral mitral annulus late diastolic velocity and A wave velocity increased in pregnant females with impaired glucose tolerance compared with normal pregnant cases. 8 Scantlebury et al reported that women with hypertensive pregnancies also had larger left atrial size and lower mitral E/A ratio after adjusting for demographic variables. 9 Preeclampsia is a form of gestational hypertension syndrome, defined as the first onset of hypertension after 20 weeks of pregnancy and with proteinuria.…”
Section: Editorialmentioning
confidence: 99%